2020
DOI: 10.2478/bhk-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

Fitness profiles of professional futsal players: identifying age-related differences

Abstract: Summary Study aim: The aim of this study was to determine the fitness profiles of senior and junior futsal players and to identify potential differences between the studied age groups. Materials and methods: 44 male futsal players from 5 professional futsal teams participated in this study. Subjects were divided into two age groups (seniors [>18 years; n = 26] vs juniors [<18 years of age; n = 18]). Players were tested for anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 36 publications
5
27
0
1
Order By: Relevance
“…Moreover, Poljskic et al [ 14 ] showed that U19 players had better results than U17 in RAG (reactive agility) test. On the other hand, there is a study that found no significant difference between juniors (<18) and seniors (>18) in specific reactive agility tests [ 33 ]. However, reactive agility is being developed until the late adolescent age, when it can reach its peak, which could be the reason for the discrepancy in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Poljskic et al [ 14 ] showed that U19 players had better results than U17 in RAG (reactive agility) test. On the other hand, there is a study that found no significant difference between juniors (<18) and seniors (>18) in specific reactive agility tests [ 33 ]. However, reactive agility is being developed until the late adolescent age, when it can reach its peak, which could be the reason for the discrepancy in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in male soccer players did not observe differences in agility performance between U19 and U17 ( 81 ) and U15 ( 83 ) age groups. In addition, adult (mean age: 28.1 ± 5.2 years) futsal players did not show higher agility performance than U19 players ( 76 ). Whereas, in studies of ( 68 ) and ( 78 ), U19 players outperformed U17 male soccer players in agility performance.…”
Section: Discussionmentioning
confidence: 77%
“…Soccer ( 50 – 53 , 55 58 , 60 – 62 , 65 , 66 , 68 , 70 73 , 77 , 79 – 84 ) was the most examined sport, with over two-thirds ( n = 25) of the 37 included studies approaching it. Athletes of other sports, such as futsal ( 76 ), Australian rules football ( 54 ), rugby league football ( 49 ), rugby union ( 63 ), badminton ( 74 ), and table tennis ( 59 ), were assessed in single studies each. Three studies included athletes of different sports ( 64 , 75 , 79 ), one included inactive subjects ( 69 ), and two studies did not report subjects' sport participation ( 32 , 67 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations